Kako Vitomil Zupan misli gledališče - Toporišič, Tomaž (Jezik in slovstvo, 2015)
The essay focuses on a seemingly simple question: How did Vitomil Zupan think theatre? The answer to this question can be found in a dialogue with the author's thoughts from his plays, theatrical writings and essays that can be linked to the ideas of 20th century theatre practitioners and theorists such as Artaud, Brecht, Kermauner, Jovanović, Taufer and Šeligo. Zupan's conceptions of drama and theatre are linked to and compared with the conceptions of theatre today. It is thus possible to establish how far-reaching his thinking about theatre was, and how productive it can be for theatre after the turn of the millennium. The centre of interest is Sholion (theatre 1972, with a particular focus on the mechanism of performance and its relation to the so-called message), his all too frequently forgotten theoretical treatise on theatre with its attractive conception of the highly dynamic relationship between drama and performance, as well as its concept of theatre as a complex phenomenon with its specific dialectic of mixed media. Drama writing must therefore be open to various ways of theatrical performance.
Keywords: Zupan, Vitomil, 1914-1987; "Sholion"; Jelinek, Elfriede, 1946-; Slovene literature; slovenska književnost; slovenski dramatiki; sodobna drama; performativna revolucija; metagledališkost; dramatik kot scenarist